Research on the design of panoramic virtual learning environment screen elements - Huang, Guan; Zhou, Li; Chen, Dan; Chen, Wen; Liu, Rui (Frontiers in Psychology, 2024)
Panoramic video and virtual reality technologies create learning environments that provide learners with an "immersive" experience. In recent years, panoramic video design to create immersive learning environments, in particular, has become an increasingly popular topic in teacher education and educational research. Previous studies have shown that panoramic virtual learning environments can be used as teaching resources in education and are effective in improving learning. However, few studies have explored the elements of panoramic virtual learning environment screens regarding the design of learning environments. Therefore, this experimental study uses eye-tracking technology to investigate how learners are guided by panoramic video elements in a panoramic virtual learning environment. The purpose of this study is to investigate whether different narration and caption presentation methods effect learners' attention, emotions and experiences. The results of the study show that when learners experience a panoramic virtual learning environment with different narration methods, the live interpretation method is more likely to attract learners' attention and bring better emotion and experience than the AI interpretation method. When experiencing a panoramic virtual learning environment with different caption presentation methods, the caption presentation methods induced learners' attention, learning emotions and experiences in the order of no caption > 120 degree caption > static following caption. Finally, the rules for optimizing the design of panoramic virtual learning environment screens are given based on the findings of the study, hoping to provide a more active learning environment for learners.